0°0’0” Making City. El tercer paisaje como forma de tejer naturaleza y ciudad/ 0°0’0” Making City. The Third Landscape as a form of Linking Nature and City - Cruz Cabrera, Marianela; Fernández Vivancos, Enrique (Revista Científica de Arquitectura y Urbanismo, 2019)
RESUMEN: La urbanización acelerada de las ciudades latinoamericanas, obliga a poner la mirada hacia partes sensibles de la misma, las llamadas periferias o bordes urbanos. El trabajo se enfoca en presentar la herramienta del Workshop Académico un espacio de discusión, intercambio de ideas y posicionamiento sobre el escenario urbano y del paisaje, desde la perspectiva del tercer paisaje, lugar de poderosas dinámicas. El workshop se desarrolló en Quito, Ecuador, en septiembre de 2018, bajo el tema 0°0’0” “Making City”. Como resultado se presentó una propuesta para recuperar y reciclar espacios existentes en la ciudad como alternativa viable hacia la diversidad, inclusividad y mejora de la calidad de vida de las personas que propugna la nueva agenda urbana para la ciudad actual y futura. ABSTRACT: Accelerated urbanization in Latin American forces us to look towards sensitive parts of its cities such as their so-called peripheries or urban edges. This essay focuses on presenting the tool derived from the Academic Workshop as a space for discussion, exchange of ideas and positioning on the urban and landscape scenarios. The analysis stems from the perspective of the third landscape, as a place of powerful dynamics. The workshop held in Quito, Ecuador in September 2018 was held under the theme 0°0’0” “Making City.” ” The workshop’s findings are a call to recover and recycle existing spaces in the city as a viable alternative to diversity, inclusiveness and improvement of the quality of life of the people that the new urban agenda advocates for the current and future city.